If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5a + 3b + -1a + -5b = 0 Reorder the terms: 5a + -1a + 3b + -5b = 0 Combine like terms: 5a + -1a = 4a 4a + 3b + -5b = 0 Combine like terms: 3b + -5b = -2b 4a + -2b = 0 Solving 4a + -2b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '2b' to each side of the equation. 4a + -2b + 2b = 0 + 2b Combine like terms: -2b + 2b = 0 4a + 0 = 0 + 2b 4a = 0 + 2b Remove the zero: 4a = 2b Divide each side by '4'. a = 0.5b Simplifying a = 0.5b
| x^4-3.5x^2+1=0 | | -3.8(2.7x-5.5)-8.4= | | z/.06=-7.98 | | y/8=3/11 | | (X+7)(X+14)=0 | | 7/4=5/b-4 | | -8a^2b-6ab+5b=0 | | 51-3x=3x | | ln(x)=ln(x-2)+ln(6) | | -4n-3(-8n+2)=134 | | 7-3y-4=5y | | 6x-(-2x)=-24 | | 51/6x=3x | | 2p^2-6p=0 | | 54n^2k+300nk-144k=0 | | (L)8LW=V | | -36p^2+136p+32=0 | | 6p+22= | | 5a^3b^3/15a^4b^2 | | 18x^6-2x^2=0 | | 1/7m=29 | | 2(2x+3)=50 | | 2(4f-8)=-21+5f | | 1/3x+7=-2 | | -5(x+5)=-5 | | (x^2)/(x^2-4)=0 | | 0=2x-24-338/x^2 | | -2x-5x+9=86 | | -4x+42=-6(x-6) | | -36=36m | | 9x+4=4x+4 | | 90d=9 |